"Becoming acquainted": The process of incorporating assistive technology into occupations. Issue 1 (2nd January 2019) - Larsen, Stina Meyer; Hounsgaard, Lise; Brandt, Åse; Kristensen, Hanne Kaae
ABSTRACT: Introduction: Previous studies have suggested that, in addition to factors such as sociocultural and physical contexts, the incorporation of assistive technology (AT) into everyday life is influenced by acceptance. Less seems to be known about the actual process by which the AT becomes incorporated. Purpose: To investigate older adults' experiences of the process of incorporating ATs into occupations. Method and material: A qualitative longitudinal approach using ethnographically inspired fieldwork with repeated interviews and participant observations was taken to explore experiences related to eight older adults' incorporation of an AT into occupations. A phenomenological-hermeneutical approach was used to interpret the data. Findings: Through the analysis, one main theme, "Becoming acquainted" and six related subthemes, "Acquaintance through use", "Drawing on previous experiences", "Engaging in valued occupations", "Encounters with others", "Regaining control over everyday life" and "Challenges in using the AT" were identified. Conclusion: Active use of the AT – or "doing" – was experienced as important to the process of, first, learning the AT's different functions and, later, engaging or re-engaging in valued occupations. Using the AT to engage in occupations had a positive impact on the participants' minds and inner selves, i.e. it influenced their "being" and enabled a connection to people and places and thereby enhanced the feeling of "belonging". All these elements contributed to a successful incorporation of the AT into occupations or to the older adults "becoming" users of AT.